2021
DOI: 10.3390/ma14185302
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Silica Specific Surface Area and Ionic Liquids on the Curing Characteristics and Performance of Styrene–Butadiene Rubber Composites

Abstract: In this work, we present the effect of silica’s specific surface area (180 m2·g−1 and 380 m2·g−1, respectively) on the crosslinking of styrene–butadiene rubber (SBR) composites, as well as their crosslink density and functional properties, such as thermal stability, damping behavior, resistance to thermo-oxidative aging, and tensile properties. Ionic liquids (ILs) with a bromide anion and different cations, i.e., 1-butyl-3-methylimidazolium (Bmi), 1-butyl-3-methylpyrrolidinium (Bmpyr), and 1-butyl-3-methylpipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…It is known that NR composites have poor resistance to thermo-oxidative aging as compared to most synthetic rubbers [ 67 ]. It has also been proven that some additives such as ILs or silanes can significantly affect the resistance of vulcanizates to the aging process [ 42 , 68 , 69 ]. Hence, the influence of biofillers, APTES and BmiCl on the resistance of NR vulcanizates to thermo-oxidative aging was studied in the next step of the research.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that NR composites have poor resistance to thermo-oxidative aging as compared to most synthetic rubbers [ 67 ]. It has also been proven that some additives such as ILs or silanes can significantly affect the resistance of vulcanizates to the aging process [ 42 , 68 , 69 ]. Hence, the influence of biofillers, APTES and BmiCl on the resistance of NR vulcanizates to thermo-oxidative aging was studied in the next step of the research.…”
Section: Resultsmentioning
confidence: 99%
“…According to Xue et al [ 75 ] imidazolium salts showed higher thermal stability than ILs with other cations. We have also confirmed that the presence of the unsaturated heterocyclic imidazolium ring in the cation facilitated the thermal stability compared to ILs having a saturated heterocyclic ring, i.e., a pyrrolidinium or piperidinium ring [ 56 , 64 ]. Thus, ILs with pyrrolidinium and piperidinium cation reduced the T 5% by 12–20 °C as compared to the vulcanizate without ILs.…”
Section: Resultsmentioning
confidence: 52%
“…Moreover, the crosslinking of the silica-filled rubber compound proceeded in a wider range of temperatures compared to the unfilled NR. The endset crosslinking temperature was approximately 2 °C higher than that of the unfilled benchmark, which was probably due to the fact that the filler network hampers the diffusion of heat and the components of the curing system through the elastomer matrix during vulcanization [ 53 , 55 , 64 ]. Considering the measurement error, nanosized silica did not significantly affect the enthalpy of crosslinking process compared to the unfilled NR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the presented work focuses on examining the synergistic effect of accelerators in silica-filled SBR composites, the methodology typically used for elastomer composites was used in the research [31][32][33].…”
Section: Preparation and Characterization Of Sbr Compositesmentioning
confidence: 99%